Histamine H2 receptor in blood cells: a suitable target for the treatment of acute myeloid leukemia - Monczor, Federico (2016)
Acute myeloid leukemia (AML) consists in a cancer of early hematopoietic cells arising in the bone marrow, most often of those cells that would turn into white blood cells (except lymphocytes). Chemotherapy is the treatment of choice for AML but one of the major complications is that current drugs are highly toxic and poorly tolerated. In general, treatment for AML consists of induction chemotherapy and post-remission therapy. If no further post-remission is given, almost all patients will eventually relapse. Histamine, acting at histamine type-2 (H2) receptors on phagocytes and AML blast cells, helps prevent the production and release of oxygen-free radicals, thereby protecting NK and cytotoxic T cells. This protection allows immune-stimulating agents, such as interleukin-2 (IL-2), to activate cytotoxic cells more effectively, enhancing the killing of tumor cells. Based on this mechanism, post-remission therapy with histamine and IL-2 was found to significantly prevent relapse of AML. Alternatively, another potentially less toxic approach to treat AML employs drugs to induce differentiation of malignant cells. It is based on the assumption that many neoplastic cell types exhibit reversible defects in differentiation, which upon appropriate treatment results in tumor reprogramming and the induction of terminal differentiation. There are promissory results showing that an elevated and sustained signaling through H2 receptors is able to differentiate leukemia derived cell lines, opening the door for the use of H2 agonists for specific differentiation therapies. In both situations, histamine acting through H2 receptors constitutes an eligible treatment to induce leukemic cell differentiation, improving combined therapies.